Vignettes and Self-Reports of Work Disability in the United States and the Netherlands - Kapteyn, Arie; Smith, James P; Soest, Arthur van (American Economic Review, 2007)
In contrast to the believed similarity in their health outcomes, workers in different Western countries report very different rates of work disability. Using new data from the United States and the Netherlands, we offer a partial resolution to this paradox. We find that observed differences in reported work disability largely stem from the fact that Dutch respondents have a lower threshold in reporting whether they have a work disability than American respondents. For those who do not suffer from pain, work disability is similar in both countries once thresholds are the same. For respondents with pain, however, a significant difference remains. (JEL J14, J28)